2021
DOI: 10.1038/s41598-021-90481-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain networks involved in the influence of religion on empathy in male Vietnam War veterans

Abstract: Humans all over the world believe in spirits and deities, yet how the brain supports religious cognition remains unclear. Drawing on a unique sample of patients with penetrating traumatic brain injuries (pTBI) and matched healthy controls (HCs) we investigate dependencies of religious cognition on neural networks that represent (1) others agents’ intentions (Theory of Mind, ToM) and (2) other agents’ feelings (Empathy). Extending previous observations that ToM networks are recruited during prayer, we find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…More recently, Cristofori et al ( 2021 ) investigated the neural interplay between empathy and personal relationship with God. Extending previous observations that theory of mind networks is recruited during prayer (Boyer, 2003 , 2008 ), the authors found that people with vmPFC damage reported higher scores on the personal relationship with God inventory (Lawrence, 1997 ) even when they were not praying.…”
Section: Highlighted Findingsmentioning
confidence: 99%
“…More recently, Cristofori et al ( 2021 ) investigated the neural interplay between empathy and personal relationship with God. Extending previous observations that theory of mind networks is recruited during prayer (Boyer, 2003 , 2008 ), the authors found that people with vmPFC damage reported higher scores on the personal relationship with God inventory (Lawrence, 1997 ) even when they were not praying.…”
Section: Highlighted Findingsmentioning
confidence: 99%
“…Some factors may even foster PD upon empathetic concern, such as (i) psychological state of the observer (especially depression) [ 104 ] (depression is frequent among radicalized young people); (ii) exposure to physical rather than psychological pain [ 109 ]; and (iii) psychological inflexibility in adolescents’ prejudices [ 110 ]. Conversely, the adoption of radical views has been shown to reduce PD [ 111 ]; therefore, PD may have an important role as an acute coping mechanism possibly involved in the radical belief system.…”
Section: Relationship Between the Sympathy/empathy System And Radical...mentioning
confidence: 99%
“…Very recent research went further to clarify reciprocal relationships between empathy and religious beliefs. To determine whether holding religious beliefs promotes cognitive flexibility and openness or biases the development of such beliefs, Cristofori et al studied neurological patients with brain lesions involving the main regions of TOM (notably the VmPFC) [ 111 ]. The authors tested two alternative hypotheses: whether empathy promotes religious belief or whether religious belief promotes greater prosocial tendencies.…”
Section: Consistency Between Empathy and Radical Beliefs And Behavior...mentioning
confidence: 99%
See 1 more Smart Citation